Correlation between social skills and emotional intelligence inregarding language learning competences - Ataç, Selçuk (My University, 2011)
As far as technical education is concerned the lack of motivation plays a significant role in terms of academic achievement and failure within the concept of language learning and teaching. In order to supply a valid source of reference for the language teacher, we, at the Vocational School of Technical Studies, have conducted a survey to find out the effects of emotional and social skills of the learners, paying particular attention to the academic achievement, emotional intelligence and social skills and found out that students with higher academic scores were also equipped with certain social skills like self esteem and empathy. While doing this literature on the area has been scanned and case studies have been performed and one to one interviews were used so as to reach formal quantitative results. This study aims at finding out the importance of social intelligence and emotional intelligence in terms of managing language learning process. To reach this goal, a research has been conducted on the students of (n=240) of two institutions of vocational education in Istanbul. In the research, participants' emotional intelligence was assessed by the Emotional Competence Inventory (ECI, 2nd Version) developed by Boyatzis and Goleman and the Resilience Scale for Adults (RSA-scale) proposed by Hjemdal, Friborg, Martinussen, and Rosenvinge. According to the results, relationship was revealed among emotional intelligence, social intelligence and language learning.
Keywords: Social Intelligence; Emotional Intelligence; Language Learning; Sosyal Zeka; Duygusal Zeka; Dil Öğrenmek